The Concept of Child Identity Education Perspective of the Qur’an; Thematic Study of Term Thifl Quranik - Asrul Asrul (Fakultas Tarbiyah, Universitas Darussalam Gontor, 2021)
Several children's quranic terms in the Al-Qur'an have meaning and relevance to contemporary children's issues. Each of these terms has a specific meaning and a specific scope for children's problems. This research focuses on studying the term thifl quranic and the signs contained in it. This research is very important considering that children's problems always leave problems. Meanwhile, studies on children's issues in the Qur'an do not refer to these Qur'anic terms comprehensively. This study aims to reveal the depth of the meaning of the term thifl in the Al Qur'an and its contribution to children's identity education. This study uses a library research method by utilizing the results of existing research related to children's problems. The results of this study indicate an interesting fact that the term thifl quranic carries a special mission among other child terms. The term thifl in the Koran is more specifically focused on the concept of child identity education. The concept of child identity education offered by the term thifl concerns physical, psychological, and social aspects of life. These three aspects affect how to educate children both at home, at school, and in the community.